2015
DOI: 10.1260/1475-472x.14.3-4.431
|View full text |Cite
|
Sign up to set email alerts
|

The Spectral Shape of Combustion Noise

Abstract: In this paper, it is proposed that the spectral shape of combustion noise is the same as the similarity spectrum of the noise from the large turbulence structures of high-speed jets. This is true regardless of the turbulence level in the combustion process, the equivalence ratio of the fuel or whether the fuel is a gas or a liquid as long as it is hydrocarbon. At the present time, the mechanism by which combustion noise is generated is still not known. So, it is not possible to prove the correctness of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…In a recent study, Tam [2015] used an empirical approach and proposed that combustion noise spectrum is similar to the noise spectrum from large turbulence structures of high-speed jets. Good agreement was found by comparing the proposed similarity spectrum and a large set of combustion noise spectra.…”
Section: Experimental Studies Of Sound Generation By Premixed Flamesmentioning
confidence: 99%
“…In a recent study, Tam [2015] used an empirical approach and proposed that combustion noise spectrum is similar to the noise spectrum from large turbulence structures of high-speed jets. Good agreement was found by comparing the proposed similarity spectrum and a large set of combustion noise spectra.…”
Section: Experimental Studies Of Sound Generation By Premixed Flamesmentioning
confidence: 99%
“…[14][15][16] Another source of indirect combustion noise due to compositional inhomogeneities which cause the transfer of chemical potential energy into acoustic energy in the accelerating flow has recently been identified in literature. [17][18][19] The spectral shape of direct combustion noise from open flames has frequently been studied, e.g., experimentally in Kotake and Takamoto 20 and Rajaram and Lieuwen 21 at varying fuels, flow parameters, and burner geometries, numerically in Schlimpert et al, 22 and empirically in Tam et al 23 Tam et al 23 analyzed experimental data from the literature and derived an empirical law for the heat release spectrum. Schlimpert et al 22 studied the heat release spectra and the acoustic response to heat release fluctuations in a low, medium, and high frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…1719 The spectral shape of direct combustion noise from open flames has frequently been studied, e.g., experimentally in Kotake and Takamoto 20 and Rajaram and Lieuwen 21 at varying fuels, flow parameters, and burner geometries, numerically in Schlimpert et al., 22 and empirically in Tam et al. 23 Tam et al. 23 analyzed experimental data from the literature and derived an empirical law for the heat release spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental studies of open, turbulent, premixed and diffusion flames have demonstrated the broadband nature of combustion noise [3][4][5][6] for a large variety of geometries and flow variables. A recent study by Tam [7] compared experimental hydrocarbon combustion noise spectra from turbulent open flames, low Mach number jets, can-type combustors, auxiliary power units and turbofan engines. This study verified that combustion noise broadband spectrum can be satisfactory modeled by the similarity spectrum of the noise from large turbulent structures in high speed jets.…”
mentioning
confidence: 99%